Different temperature dependence of the bacterial brGDGT isomers in 35 Chinese lake sediments compared to that in soils. (May 2018) - Dang, Xinyue; Ding, Weihua; Yang, Huan; Pancost, Richard D.; Naafs, B. David A.; Xue, Jiantao; Lin, Xiao; Lu, Jiayi; Xie, Shucheng
Highlights: 5- and 6-methyl brGDGTs measured in 35 Chinese lakes. Seasonal bias towards warm months in cold region lakes. Different responses to temperature between lakes and soils. Abstract: During the last decade, the distribution of branched glycerol dialkyl glycerol tetraethers (brGDGTs) in lacustrine sediments has been widely used to reconstruct past variations in lake temperature. A prerequisite for the application of brGDGTs to lacustrine paleoclimate reconstructions is to understand the sources of brGDGTs in lake systems and the processes that influence their distribution. In this study, we investigated the distribution of brGDGTs in core-top sediments from 35 lakes across China, with a broad mean annual air temperature (MAAT) range, but a constrained pH range, to explore the effect of temperature. The results reveal a contrasting response of MBT′5ME and MBT′6ME to temperature in lake environments compared to that in soils. The sedimentary distributions of 5- and 6-methyl brGDGTs exhibit different relationships with temperature, with most of the latter being correlated to MAAT while the former responding to temperature by only hexamethylated compounds. In both global and Chinese soils, most 6-methyl brGDGTs have no relationship with MAAT, but the distribution of 5-methyl brGDGTs is correlated with MAAT. The different behaviors suggest that communities producing 5- or 6-methyl brGDGTs might be different in lakes and soils. In addition, in lakes from cold regions (MAAT < 5 °C), the brGDGT distributions correlate only with warm season temperatures (April to October) but exhibit no correlation with cold seasons, suggesting a seasonal bias in brGDGT production in these lakes. This bias towards the warm season is not found in lakes from warmer regions (MAAT > 5 °C). Based on these results we propose new temperature calibrations for paleotemperature reconstructions in Chinese alkaline lakes.